(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2024)
In Kuwait, there has been an increase in the consumption of fast and processed foods, resulting in a rise in non-communicable diseases. To make informed policy decisions, it is crucial to establish a comprehensive local food database. The purpose of this study was to create a local food composition database The database includes nutrient values for locally processed foods from major Kuwaiti food processing lines. We collected nutrition information from 518 food products’ labels of 16 food companies representing Kuwait’s primary food processing lines. Following the USDA Food and Nutrient Database for Dietary Studies, we created a Microsoft Excel spreadsheet to establish a food composition database for locally processed food. The products’ label information was grouped into six food groups. Each food group’s products were classified into four classes based on their level of processing: Minimally processed food, processed food, Culinary processed food, and Ultra-processed food, according to the NOVA classification system. About 74.7% of the collected products were Ultra-processed food, which is high in saturated fats, sodium, and calories, and has negative impacts on global health and nutrition. This is the first study to use the NOVA in Kuwait, and the results will be recommended to policymakers for product classification in the market, visible to consumers as stickers or codes to raise awareness of highly processed food. Moreover, Results are ready to be incorporated into the ESHA food processing system in future research to be accessible to researchers in the nutrition field. This generated database will be a valuable tool for researchers and policymakers to establish preventive actions to reduce the prevalence of NCDs in the population and increase consumers’ awareness of processed food.